A mussel-inspired wet-adhesion hydrogel with hemostasis and local anti-inflammation for managing the development of acute wounds. (January 2022) - Zhu, Jieyu; Zhong, Kaijing; Zong, Yuan; Wang, Shunhua; Yang, Huiyu; Zhen, Li; Tao, Siying; Sun, Lizhong; Yang, Jiaojiao; Li, Jiyao
Graphical abstract: Highlights: A wound dressing hydrogel was prepared by one-step assembly of tannic acid, silk fibroin and diclofenac potassium. The composite hydrogel has excellent underwater adhesion ability, hemostasis function and favorable biocompatibility both in vivo and in vitro . The adhesive can significantly down-regulate inflammatory cytokines in vivo and in vitro, matching the needs of acute wounds. Abstract: Acute wounds often cause overdeveloped inflammation, which can adversely affect wound healing. Wound dressing has been widely used, but it is still challenging to achieve an effective anti-inflammation treatment due to the complex wet environment of the wounds. Here, we proposed a wound sealant, tannic acid-silk fibroin-diclofenac potassium (TA-SF-DP, TSD) hydrogels. And evaluated their wet-adhesion performance and the potency on inflammation regulation through comprehensive mechanical tests and molecular biology research. The TSD hydrogels exhibited an outstanding wet-adhesion property to porcine soft tissues even in blood (up to (38.6 ± 4.6) kPa) and strong hemostatic ability in rat tail truncation model ((reduced hemostasis time from (685 ± 55) s to (160 ± 72) s and reduced blood loss from (0.59 ± 0.07) g to (0.06 ± 0.03) g compared with the gauze group). Simultaneously, the hydrogels showed satisfactory anti-inflammatory effects (sustained reduction of inflammation at 6 h and 24 h, generally the peak and persistent state of severe postoperative reaction, respectively), which works by releasing non-steroidal anti-inflammatory drug DP conforming to physiological needs. Combined with the wet adhesion, anti-inflammatory property and remarkable biocompatibility, the TSD hydrogels have the potential to be a clinical wound sealant to manage acute wounds.